2011
DOI: 10.1039/c0lc00348d
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidics analysis of red blood cell membrane viscoelasticity

Abstract: In this work, a microfluidic system to investigate the flow behavior of red blood cells in a microcirculation-mimicking network of PDMS microchannels with thickness comparable to cell size is presented. We provide the first quantitative description of cell velocity and shape as a function of the applied pressure drop in such devices. Based on these results, a novel methodology to measure cell membrane viscoelastic properties in converging/diverging flow is developed, and the results are in good agreement with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
92
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 32 publications
4
92
0
Order By: Relevance
“…Some examples are the measurement of the RBC cellular trajectories and deformation under a transient high shear stress in microchannels with a rectangular cross-section 20,21 and the determination of cell deformability of a single RBC flowing in a microfluidic device with a microchannel thickness comparable to the RBC size. 19 Studies focusing on the effect of extensional flow field on RBC flow and deformability are scarce despite extensional flow often being present in the microcirculation, particularly when there is a sudden change in geometry, e.g., in stenosis and in microvascular networks composed of short irregular vessel segments linked by numerous bifurcations. In converging flows such as those found in microstenoses, extensional flow can be generated due to the dramatic change of velocity when the fluid flows from a wide to a narrow region of the channel.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some examples are the measurement of the RBC cellular trajectories and deformation under a transient high shear stress in microchannels with a rectangular cross-section 20,21 and the determination of cell deformability of a single RBC flowing in a microfluidic device with a microchannel thickness comparable to the RBC size. 19 Studies focusing on the effect of extensional flow field on RBC flow and deformability are scarce despite extensional flow often being present in the microcirculation, particularly when there is a sudden change in geometry, e.g., in stenosis and in microvascular networks composed of short irregular vessel segments linked by numerous bifurcations. In converging flows such as those found in microstenoses, extensional flow can be generated due to the dramatic change of velocity when the fluid flows from a wide to a narrow region of the channel.…”
mentioning
confidence: 99%
“…The distinct advantage of the microfluidic devices to test a large number of cells using only a small amount of blood has prompted a vast amount of research in this field. 3,8,12,15,[19][20][21] However, most of the proposed devices focus mainly on the effect of shear flow alone. Some examples are the measurement of the RBC cellular trajectories and deformation under a transient high shear stress in microchannels with a rectangular cross-section 20,21 and the determination of cell deformability of a single RBC flowing in a microfluidic device with a microchannel thickness comparable to the RBC size.…”
mentioning
confidence: 99%
“…Red blood cells (RBCs) play an important role in cell metabolism and aerobic respiration [1,2]. The physical and mechanical features of RBCs have been regarded as an important indicator in the studies of bio-processes, pathology, and toxicology [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Abkarian et al [23][24] experimentally observed the alterations of deformability between healthy and unhealthy RBC in a microchannel. Later, the deformation of RBC subjected to pressure-driven flows in a microchannel has been comprehensively studied [25][26][27]. Recently, Chen et al [28] fabricated a lab-on-a-chip device with a capillary network to study the RBC hydrodynamics.…”
Section: Introductionmentioning
confidence: 99%